The Legality of Electronic Signature (Digital Signature) Judging from Civil Procedure Law - Basir; Osgar Sahim Matompo; Maisa (Program Pascasarjana Universitas Muhammadiyah Palu, 2022)
This study aims to determine and analyze the legal position and power of digital signatures as evidence according to government regulation Number 82 of 2012 and to determine and analyze the legal requirements for the operation of electronic systems and transactions according to government regulations Number 82 of 2012. The results of the study found that an electronic signature will have a perfect legal force if it meets the elements described in Article 53 paragraph (2) of Government Regulation No. 82 of 2012 so if it does not meet the elements of Article 53 paragraph (2) of Government Regulation No. 82 of 2012 then the implementation of the digital signature can be said to be juridical (legal defects). The legal requirements for electronic systems and transactions are based on Government Regulation 82 of 2012. According to what is described in Article 41 paragraphs (1) to (3) of government regulation Number 82 of 2012 concerning the operation of electronic systems and transactions as long as they fulfill these provisions, they can perform legal electronic transactions which are very relevant to people's lives and can make it easier for the public to conduct electronic transactions and various other electronic transactions. In addition, if the users feel that their rights have been violated during exertion, they can make reports and complaints to the authorities in the field of information technology and electronic transactions in accordance with what is described in Article 43 paragraphs (1) to (5) of Law Number 19 of 2016 on the amendment to Law Number 11 of 2008 regarding information and electronic transactions. The research advice is the need for socialization related to digital signatures by the government at all levels of society, especially in rural areas. There needs to be a definite and clear legal force from an uncertified electronic signature so that in its application it is used effectively and the provisions of laws and regulations by users in conducting electronic transactions in order to get security and definite services.